Operational plan for UNAIDS action framework : addressing women, girls, gender equality, and HIV (UNAIDS GenevaCH, 2009)
Addresses the persistent gender inequality and human rights violations that put women and girls at greater risk and vulnerability to HIV, and threaten the gains that have been made in preventing HIV transmission and increasing access to anti-retroviral treatment.
Keywords: HIV